2007
DOI: 10.1085/jgp.200709755
|View full text |Cite
|
Sign up to set email alerts
|

A Na+ Channel Mutation Linked to Hypokalemic Periodic Paralysis Exposes a Proton-selective Gating Pore

Abstract: The heritable muscle disorder hypokalemic periodic paralysis (HypoPP) is characterized by attacks of flaccid weakness, brought on by sustained sarcolemmal depolarization. HypoPP is genetically linked to missense mutations at charged residues in the S4 voltage-sensing segments of either CaV1.1 (the skeletal muscle L-type Ca2+ channel) or NaV1.4 (the skeletal muscle voltage-gated Na+ channel). Although these mutations alter the gating of both channels, these functional defects have proven insufficient to explain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
206
1
3

Year Published

2008
2008
2015
2015

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 155 publications
(224 citation statements)
references
References 31 publications
14
206
1
3
Order By: Relevance
“…Two recent studies have suggested that a gating pore current may be important in the pathogenesis of HypoPP, 13,14 and our data are fully consistent with this hypothesis. In response to depolarizing voltages, S4 segments undergo a conformational change that moves these segments outwards through a gating pore (omega pore) which leads to the opening of the central pore of the channel (alpha pore).…”
Section: Figuresupporting
confidence: 92%
See 1 more Smart Citation
“…Two recent studies have suggested that a gating pore current may be important in the pathogenesis of HypoPP, 13,14 and our data are fully consistent with this hypothesis. In response to depolarizing voltages, S4 segments undergo a conformational change that moves these segments outwards through a gating pore (omega pore) which leads to the opening of the central pore of the channel (alpha pore).…”
Section: Figuresupporting
confidence: 92%
“…However, evidence also exists that at least some of these mutations allow an abnormal cation flux to pass through the aqueous omega pore that lines the voltage sensor. 13,14 The full spectrum of HypoPP mutations has not been defined. In particular, it remains to be determined whether the gating pore cation leak hypothesis accounts for all cases.…”
mentioning
confidence: 99%
“…1A). Design of these charge neutralized (CN) Nav1.4 mutants, e.g., domain I (DI-CN) was motivated in part by recent findings that mutation of specific charged residues in the S4 segments allows state-dependent ion flux through the voltage-sensing domains (39)(40)(41)(42). These currents directly report the movement of voltage sensors and are referred to as gating pore currents (also omega currents) to distinguish them from the canonical ionic currents through the central pore.…”
Section: Resultsmentioning
confidence: 99%
“…How mutations of cationic amino acids in the voltage sensor cause the paradoxical depolarization of sarcolemma during hypokalemia, however, had been an enigma. Recent studies showing that mutations in the voltage sensor create an aberrant conducting pore ("gating pore") that allows passage of small cations (Na ϩ and H ϩ ) at hyperpolarized resting membrane potentials (15,16) provide a mechanistic explanation for paradoxical depolarization of sarcolemma during hypokalemic attacks.…”
Section: Discussionmentioning
confidence: 99%